2013
DOI: 10.1097/pas.0b013e31829ab1c1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CDX2/CK20 Expression Is Associated With Poorly Differentiated Carcinoma, the CpG Island Methylator Phenotype, and Adverse Prognosis in Microsatellite-unstable Colorectal Cancer

Abstract: Several previous studies have demonstrated that the CDX2-negative (CDX2) and/or CK20-negative (CK20) phenotypes of colorectal cancers (CRCs) might be associated with high levels of microsatellite instability (MSI-H). The aim of this study was to investigate the clinicopathologic and molecular features of MSI-H CRCs with different CDX2/CK20 expression statuses. The CDX2 and CK20 expression statuses were immunohistochemically evaluated in 109 MSI-H CRC tissue samples, and the correlations of these statuses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 33 publications
14
66
0
Order By: Relevance
“…Recently, the CK20 protein has received increased interest due to its highly specific expression in both colorectal and gastric cancers (Kim et al, 2009;Sun et al, 2012;Kim et al, 2013;Tunca et al, 2013). In these cells, CK20 protein is highly expressed, with features including irregular modulation, loss of polarity, and diffuse distribution (Šamija et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CK20 protein has received increased interest due to its highly specific expression in both colorectal and gastric cancers (Kim et al, 2009;Sun et al, 2012;Kim et al, 2013;Tunca et al, 2013). In these cells, CK20 protein is highly expressed, with features including irregular modulation, loss of polarity, and diffuse distribution (Šamija et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, such correlations in a non-smoker at a young age cannot be proven and thus this case illustrates a rare incidence of mucinous adenocarcinoma with no known risk factor. CK20 and CDX2 were tumor markers found to be expressed in the tumor from the present patient and have previously been shown to be prominent in some other malignancies, such as colorectal cancer (7). It therefore raises the hypothesis, whether a family history of colon cancer increases the risk of bladder cancer at a younger age and whether a patient with a positive family history of colon cancer with particular markers should have early screening for bladder cancer.…”
Section: Discussionmentioning
confidence: 82%
“…5 In our previous study, 6 we demonstrated that MCPyV-negative MCCs show more poorly differentiated features, such as severe nuclear atypia and pleomorphism, than MCPyV-positive MCCs. The combination of CK20 expression loss and MCPyV negativity may be associated with the poorly differentiated MCC features.…”
mentioning
confidence: 79%